2018
DOI: 10.1109/tnsre.2018.2829804
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Spectroscopy Study of Cortical Excitability During Electrical Stimulation-Assisted Cycling for Neurorehabilitation of Stroke Patients

Abstract: In addition to generating functional limb movement via electrical stimulation, other research proposed lower intensity stimulation for stroke patients from proprioceptive and neuro-biofeedback aspects. This paper investigates the effects of different intensity levels of electrical stimulation during passive cycling on cortical activation using multichannel near infrared spectroscopy (NIRS) covering premotor cortex, supplementary motor area, sensorimotor cortex (SMC), and secondary sensory cortex (S2) regions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…What's interesting is that NMES applied on muscles also affects Electroencephalogram (EEG) oscillatory ( 8 ), which verifies that NMES on the muscles can activate related brain area, and this activation pattern represented by ERD is similar to that under active movement. Lo et al used near infrared spectroscopy (NIRS) to investigate cortical activation of different-intensity electrical stimulations ( 9 ). These studies evaluated the efficacy of NMES from the view of brain activation.…”
Section: Introductionmentioning
confidence: 99%
“…What's interesting is that NMES applied on muscles also affects Electroencephalogram (EEG) oscillatory ( 8 ), which verifies that NMES on the muscles can activate related brain area, and this activation pattern represented by ERD is similar to that under active movement. Lo et al used near infrared spectroscopy (NIRS) to investigate cortical activation of different-intensity electrical stimulations ( 9 ). These studies evaluated the efficacy of NMES from the view of brain activation.…”
Section: Introductionmentioning
confidence: 99%
“…282 Comparing the electrical stimulation intensity during the rehabilitation of stroke patients while they were performing the cycling task, an intensity of 10 mA resulted in better cortical excitations compared to a higher intensity of 30 mA. 283…”
Section: Cycling Taskmentioning
confidence: 99%
“…In recent years, brain imaging techniques such as diffusion tensor imaging, 14,15 electroencephalogram, 16,17 and functional magnetic resonance imaging 18–21 have been used to determine a recovery model after stroke, which could classify the anatomy, function, chemistry, and connectivity of the brain 22 . Studies demonstrated that stroke affected the characteristics of the whole brain and the brain network, and the process of injury and recovery was related to the structural and functional reorganization of the brain 23–25 . Use‐dependent plastic brain reorganization has been widely confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…fNIRS is a non-invasive and portable method for measuring brain function and can be used to evaluate brain function remodeling in patients with cortical and subcortical stroke diseases. 24,25,28,29 With the introduction of a graph theory model in the CNS network, it is possible to describe the important attributes of complex systems by quantifying the topologies represented by the network. 17,30,31 Complex brain network data sets include nodes that represent anatomical areas and edges that represent anatomical, functional or effective connectivity (EC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation